ISLAM IN THE CASPIAN AND THE CAUCASIAN FOOTHILLS BORDERLAND: SOCIAL AND RELIGIOUS REVIVAL ON THE FRINGES OF THE MUSLIM WORLD - MAGOMEDOV, Arbakhan; VIKTORIN, Viktor (CENTRAL ASIA AND THE CAUCASUS, 2005)
Islam is rapidly gaining weight across the world. Islamophobia is escalating just as rapidly in the West, while in Russia certain highly influential segments of its political class have begun aping the West. By 2004, the unchecked wave developed into anti-Islamic hysteria. After writing The Rage and the Pride in the wake of 9/11, Italian journalist Oriana Fallaci produced an anti-Muslim Western manifesto. She poured her hatred out on Islam and the Islamic world and addressed her affection and pride to the West. Her ideas are limited to only one thought: an anti-Islamic struggle without conditions and without mercy. In Russia, certain sources have done their best to familiarize the Russian public with her ideas. Vagrius Publishers put out a Russian translation of her book in 2004.1 We can only marvel at the tenacity of the anti-Islamic and anti-Islamist ideas: the passions bring to mind the atmosphere of the anti-Communist “witch hunt” of the early 1990s. In 2002, guided by her anti-communist syndrome, Margaret Thatcher tagged Islamism as “new Bolshevism.”2 Like many others, Daniel Pipes equated fascism and Islamism in his article “Contemporary Fascism” translated and published in the Moskovskiy komsomolets newspaper.3 In the West, people no longer distinguish between Islamism and fascism—It was Alexey Malashenko who familiarized the Russian audience with the state of affairs in this sphere. In Russia, it is the media controlled by the liberal Russophobic circles that are zealously promoting anti-Muslim sentiments. The best evidence of this was the Vremena program run by famous TV personality Vladimir Pozner. In the fall of 2004, he suggested that the Islamists as a whole, and the Muslims living in Europe, in particular, should be treated with more severity. Some of the members of Russia’s Muslim clergy went as far as accusing the anchorman and the ORT channel of deliberate anti-Muslim propaganda. The National Organization of Russia’s Muslims (NORM) circulated a statement in which it called on the country’s leaders “to revise in the most radical way the information policies of the state-owned TV channels with respect to Islam.”